Tyrosine bioconjugation – an emergent alternative - Szijj, Peter A. (Org Biomol Chem, 2020)
Protein bioconjugation is an increasingly important field of research, with wide-ranging applications in areas such as therapeutics and biomaterials. Traditional cysteine and lysine bioconjugation strategies are widely used and have been extensively researched, but in some cases they are not appropriate and alternatives are needed or they are not compatible with one another to enable the formation of dually (and distinctly) modified dual-conjugates (an increasingly desired class of bioconjugates). Here we review the heretofore less explored approach of tyrosine bioconjugation, which is rapidly becoming a constructive alternative/complement to the more well-established strategies. Herein we present an overview of the field, and then focus on promising recent methods that can achieve high conversion and chemoselectivity. This suggests that not only can tyrosine bioconjugation be used in conjunction with cysteine and lysine modification to obtain proteins with multiple different modifications, it is also becoming a stand-alone alternative to these more traditional methods.